A comprehensive overview of the relationship between RET gene and tumor occurrence - Zhao, Lu; Wang, Na; Zhang, Dou; Jia, Yingjie; Kong, Fanming (Frontiers in Oncology, 2023)
RET gene plays significant roles in the nervous system and many other tissues. Rearranged during transfection (RET) mutation is related to cell proliferation, invasion, and migration. Many invasive tumors (e.g., non-small cell lung cancer, thyroid cancer, and breast cancer) were found to have changes in RET. Recently, great efforts have been made against RET. Selpercatinib and pralsetinib, with encouraging efficacy, intracranial activity, and tolerability, were approved by the Food and Drug Administration (FDA) in 2020. The development of acquired resistance is inevitable, and a deeper exploration should be conducted. This article systematically reviewed RET gene and its biology as well as the oncogenic role in multiple cancers. Moreover, we also summarized recent advances in the treatment of RET and the mechanism of drug resistance.